The Rho-Dependent Transcription Termination Is Involved in Broad-Spectrum Antibiotic Susceptibility in Escherichia coli - Hafeezunnisa, Md.; Sen, Ranjan (Frontiers in Microbiology, 2020)
One of the major ways of acquiring multidrug resistance in bacteria is via drug influx and efflux pathways. Here, we show that E. coli with compromised Rho-dependent transcription termination function has enhanced broad-spectrum antibiotic susceptibility, which arises from the inefficient TolC-efflux process and increased permeability of the membrane. The Rho mutants have altered morphology, distinct cell surface, and increased levels of lipopolysaccharide in their outer membrane, which might have rendered the TolC efflux pumps inefficient. These alterations are due to the upregulations of poly-N-acetyl-glucosamine and lipopolysaccharide synthesis operons because of inefficient Rho functions. The Rho mutants are capable of growing on various dipeptides and carbohydrate sources, unlike their WT counterpart. Dipeptides uptake arises from the upregulations of the di-peptide permease operon in these mutants. The metabolomics of the Rho mutants revealed the presence of a high level of novel metabolites. Accumulation of these metabolites in these Rho mutants might titrate out the TolC-efflux pumps, which could further reduce their efficiency. We conclude that the transcription termination factor, Rho, regulates the broad-spectrum antibiotic susceptibility of E. coli through multipartite pathways in a TolC-dependent manner. The involvement of Rho-dependent termination in multiple pathways and its association with antibiotic susceptibility should make Rho-inhibitors useful in the anti-bacterial treatment regimen.